MEANING OF THE TWENTIETH CENTURY the great transition. - Boulding, Kenneth E. (Kenneth Ewart), 1910-1993 (World perspectives, 2021)
Originally published in 1965 and written by a noted economist and leader in the field of conflict resolution, this book traces the forces which have brought the 20th century post-civilisation' into being: the ever-increasing power of science and the scientific attitude, the global communication network, the high efficiency of industrial societies. New conditions pointed to a life of ease but also enormous problems. The book discusses how though our technical resources have become immense, social and psychological conflicts remain. The author's training in psychology and economics combines with a deep sense of history to create a book which is as relevant now as when it was first published.